Structure and magnetism of copper substituted cobalt ludwigite Co3O2BO3 - Ivanova, N.B.; Kazak, N.V.; Knyazev, Yu.V.; Velikanov, D.A.; Vasiliev, A.D.; Bezmaternykh, L.N.; Platunov, M.S. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2013)
The single crystals Co3O2BO3 with partial (4%) substitution of Co by Cu ions were synthesized by the flux technique. X-ray diffraction and magnetic properties investigations were carried out. The x-ray diffraction measurements have shown that Cu clearly prefers only one from four nonequivalent crystallographic positions with the smallest electric field gradient. The ferrimagnetic ordering near TN 43 K and high magnetic hardness in this magnetic phase are similar to Co3O2BO3. The small reduction of the effective magnetic moment was revealed under copper substitution.